Islamic Religious Education Teacher's Experience in Implementing Differentiated Learning - Klis Dianti; Ruslan Ruslan; Nasaruddin Nasaruddin (Yayasan Pendidikan Bima Berilmu, 2025)
The research aims to examine the response of Islamic Religious Education teachers' experiences in implementing differentiated learning in the classroom: a case study of SND INPRES Tololara. The focus of this research is how the experience of Islamic Religious Education teachers in implementing differentiated learning. Using a qualitative approach that emphasizes natural reality, and data collection techniques include observation, interviews, documentation, and data analysis techniques by reviewing the results in the collected data that detect topics and patterns that emerge. The results of this study indicate that Islamic Religious Education teachers in their experience to identify student needs use diagnostic assessment to find out the background of students. In the strategy of implementing differentiated learning, Islamic Education teachers use four aspects of learning, namely: content, process, product and learning environment. In his experience, Islamic Education teachers have challenges or obstacles, namely, lack of strategies, limited time and resources, the solution is to apply the four aspects above so that Islamic Education teachers can change learning according to their needs because everything is under the control of the teacher.